The IMPACT OF PLASTIC BANKING IN INCOME: A CASE STUDY OF THREE BARANGAYS IN NAGA CITY - Magpayo, Michaella Maryly; Martinez, Neslie; Virtucio, Anne Floreine; Rosete, Marie Antionette (Journal of Industrial Engineering & Management Research, 2022)
Naga City, Camarines Sur generates roughly 80 tons of garbage per day and is heavily polluted with persistent floods due to improper waste disposal. Nearing the city landfill’s maximum capacity, the city’s Solid Waste Management Office (SWMO) set waste management programs to efficiently manage waste. One of which is the Plastic Banking Project, a public-private partnership for waste diversion and income generation in local communities. Plastic Bank is dedicated to stop ocean-bound plastics and reduce poverty through their recycling ecosystem. This study aims to analyze the impact of the Plastic Banking Project on its contributions to the income in the three partner barangays through the registered and unregistered plastic bank members. Multiple Regression Model is used to determine the impact of the project on being a formal register member of Plastic Bank. This study proves that an increase in collected solid waste kilos per month increases monthly income. On the other hand it found out that labor hours and social benefit tokens had no relationship with monthly income. However in the descriptive analysis of the study, the researchers found out that the majority of the respondents state that being an active collector for the plastic banking project, impacts them through additional income and benefits and can engage more people to turnover solid waste in Plastic Bank.